Sensitivity to an inhibitor of translation elongation in solid and hematologic cancers - Nathan Gomes; Barbara Frederick; John Tentler; Tin Tin Su (Scientific Reports)
Abstract Inhibitors of protein synthesis hold promise for cancer therapy because many cancer driver proteins are unstable and blocking synthesis leads to their depletion. We described previously SVC112, a small molecule inhibitor of translation elongation that inactivates Head and Neck Squamous Cell Carcinoma (HNSCC) stem cells in vitro and prevents the regrowth of HNSCC tumor xenografts in mice after radiation treatment. Here we report that SVC112 also shows activity on its own (without radiation) but with a 1600-fold range in growth inhibition among cancer cell lines of various origins. Our efforts to define molecular correlates of SVC112 sensitivity found that basal expression of apoptosis/survival factors correlates with SVC112-induced apoptosis in hematologic cancer cell lines, while phosphorylation of c-Myc correlates with sensitivity to SVC112 in colorectal cancer cell lines. Apoptosis induction by SVC112 predicts tumor growth control and survival benefit in mouse xenograft models. We suggest a paradigm wherein utility of translation inhibitors is defined by (1) inherent dependence of cancer cells on specific survival factors and (2) post-translational modifications that affect the stability of oncogenic driver proteins.